2020
DOI: 10.1080/15538362.2019.1701615
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Morphological Traits and Fruit Metabolites in Eleven Fig Varieties (Ficus Carica L.)

Abstract: In the present study, morphological traits, organic acids, sugars, total phenols, total flavonoids, total anthocyanins, total anthocyanidins, antioxidant activity and color parameters such as lightness (L*), Chroma (c*) and hue angle (h°) were investigated in 11 local and introduced fig cultivars cultivated in Moroccan climate. Since only limited information on that topic is available in the literature, this study was performed in order to compare local clones with some of introduced varieties based on their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…reported that the fruit weight value ranged between (16.49 and 77.7 g), and an average value of fruit length and width 43 and 40 mm respectively. Similar and partial difference was found with the results reported by LahcenHssaini, Chara , et al, (2020), that the highest fruit weight 87.03g and lowest value 12.4g. The fruit length and width were changed from (21.34 to 48.83 mm) and (25.93 to 61.58 mm) respectively.…”
supporting
confidence: 91%
“…reported that the fruit weight value ranged between (16.49 and 77.7 g), and an average value of fruit length and width 43 and 40 mm respectively. Similar and partial difference was found with the results reported by LahcenHssaini, Chara , et al, (2020), that the highest fruit weight 87.03g and lowest value 12.4g. The fruit length and width were changed from (21.34 to 48.83 mm) and (25.93 to 61.58 mm) respectively.…”
supporting
confidence: 91%
“…In order to further understand the findings above-stressed, the interactions between the experimental design factors, irrigation treatment (I), cultivar (C) and year experiment (Y) and their impacts on the herein investigated traits were assessed using the three-way analysis of variance (Table 6). As being disposed of having the most general applicability, the Wilks's lambda (λ) was used to evaluate the significance of each interaction level between the model factors (Todorov and Filzmoser, 2010;Hssaini et al, 2020). All factors and their interactions showed statistically significant impact on the whole model (p < 0.001).…”
Section: Interactions Between the Experimental Design Factorsmentioning
confidence: 99%
“…Anthocyanin content, mainly cyanidin-3-rutinoside; flavanols, particularly quercetin-rutinoside; phenolic acids such as chlorogenic acid; flavones such as luteolin and apigenin-rutinoside are reported as the main phenolic compounds identified in fresh figs [ 20 ]. Morocco, the third fig producer with more than 85,172 tons, is identified in historical sources as a fig cultivation area and is still today one of the most important fig diversity hotspots, which contains a large number of typical local varieties [ 21 ]. This germplasm was basically assessed using morphological and molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main aims of the present study were to (i) determine the phenolic compounds and in vitro antioxidant activity over peels and pulps of an ex-situ fig collection of 25 cultivars, (ii) investigate their concentration and availability between the two parts of the fruit, (iii) determine potential correlations with antioxidant potency and chromatic coordinates and finally (iv) to identify the most discriminant of them. Despite numerous studies reported the phenolic profile of fig accessions growing worldwide [ 17 , 18 , 19 , 20 , 21 ], very few reports have addressed the bioavailability of these bioactive compounds with respect to their partitioning in different parts of the fruit, within a large screening scheme aiming to correlate them to antioxidant potency with regards to their chromatic coordinates and the phenotypic factor. In this respect, this work is the first report on fig chemotypic diversity based on the partitioning of phenolic compounds, chromatic coordinates and antioxidant activity between peel and pulp of a large sample number of cultivars growing in Morocco, using a chemometric approach.…”
Section: Introductionmentioning
confidence: 99%